2019
DOI: 10.1021/acs.est.9b01276
|View full text |Cite
|
Sign up to set email alerts
|

Unprocessed Atmospheric Nitrate in Waters of the Northern Forest Region in the U.S. and Canada

Abstract: Little is known about the regional extent and variability of nitrate from atmospheric deposition that is transported to streams without biological processing in forests. We measured water chemistry and isotopic tracers (δ18O and δ15N) of nitrate sources across the Northern Forest Region of the U.S. and Canada and reanalyzed data from other studies to determine when, where, and how unprocessed atmospheric nitrate was transported in catchments. These inputs were more widespread and numerous than commonly recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 96 publications
3
29
0
1
Order By: Relevance
“…Based on our own simulations for forested areas within our study area, we suggest that the reemission of deposition NH 3 can be safely ignored considering high use efficiency of nitrogen by plants and that the nitrate deposited in these forested areas can rapidly transport to streams and waters without being biologically transformed (Rose et al, ; Sebestyen et al, ). Significant atmospheric nitrate deposition has also been observed that dissolved in waters at the forest regions, with high spatial and temporal variations (Sebestyen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our own simulations for forested areas within our study area, we suggest that the reemission of deposition NH 3 can be safely ignored considering high use efficiency of nitrogen by plants and that the nitrate deposited in these forested areas can rapidly transport to streams and waters without being biologically transformed (Rose et al, ; Sebestyen et al, ). Significant atmospheric nitrate deposition has also been observed that dissolved in waters at the forest regions, with high spatial and temporal variations (Sebestyen et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the gaseous forms emit back to the atmosphere (Saha et al, 2017;Maavara et al, 2018). Denitrification requires anoxic conditions and does not occur as much in shallow soils owing to the pervasive presence of O2 (Sebestyen et al, 2019); it can become prevalent however under extremely wet conditions and in O2-depleted groundwater systems. In soils, P can be in organic form (e.g., leaves), sorbed (on fine soil particles), dissolved in water, or in solid forms as P-containing minerals (Figure 3).…”
Section: Biogeochemical Reactive Transport Equationsmentioning
confidence: 99%
“…Therefore, we examined the proportion of NO 3 − atm to total NO 3 − and the flux of NO 3 − atm in waters that pass through forest canopies and surface soils in a natural coniferous-broadleaved mixed forest by using triple oxygen isotopes of NO 3 − . The results showed that the dominant source of NO 3 − in the water samples switched from NO 3 − atm to NO 3 − produced by nitrification when the water passed through the forest Many studies have examined the relationship between atmospheric N deposition and N export from forest ecosystems (Aber et al, 2003;Campbell et al, 2004;Dise & Wright, 1995;Dise et al, 2009;Grigal, 2012;Mitchell et al, 1997;Rose et al, 2015;Sebestyen et al, 2019;Tsunogai et al, 2014). Some of these studies reported that N export increases with increasing N deposition (Dise & Wright, 1995;Dise et al, 2009;Grigal, 2012;Mitchell et al, 1997), while other studies reported substantial variations in N export with similar N deposition rates (Aber et al, 2003;Campbell et al, 2004;Grigal, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the δ 18 O value of NO 3 − in a sample is known to increase during biological processes such as plant and microbial assimilation of NO 3 − and denitrification (Granger et al, 2008(Granger et al, , 2010 (Costa et al, 2011;Michalski et al, 2004;Nakagawa et al, 2013Nakagawa et al, , 2018Tsunogai et al, 2010Tsunogai et al, , 2016 (Michalski et al, 2003(Michalski et al, , 2004. Moreover, Δ 17 O is stable during mass-dependent isotope fractionation processes such as assimilation and denitrification (Michalski et al, 2004 (Rose et al, 2015;Sebestyen et al, 2019;Tsunogai et al, 2014). However, the dynamics of NO 3 − atm and its relationship with NO 3 − re from the forest canopy to the mineral soil are considerably understudied, despite highly dynamic N cycling.…”
Section: Introductionmentioning
confidence: 99%